2020
DOI: 10.1186/s12917-020-02550-w
|View full text |Cite
|
Sign up to set email alerts
|

In-gel digestion coupled with mass spectrometry (GeLC-MS/MS)-based salivary proteomic profiling of canine oral tumors

Abstract: Background Various types of oral tumors, either benign or malignant, are commonly found in dogs. Since saliva directly contacts the tumors and saliva collection is non-invasive, easily accessible and cost effective, salivary biomarkers are practical to be used for the diagnosis and/or prognosis of these diseases. However, there is limited knowledge of protein expression in saliva for canine oral tumors. The present study aimed to investigate novel biomarkers from the salivary proteome of dogs with early- and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…MASCOT software, version 2.2 (Matrix Science, London, UK), was used to search the peptide sequences against the NCBI mammal database for protein identification. Taxonomy (mammals), enzyme (trypsin), variable modifications (oxidation of methionine residues), mass values (monoisotopic), protein mass (unrestricted), peptide mass tolerance (1.2 Da), fragment mass tolerance (±0.6 Da), peptide charge state (1+, 2+ and 3+) and maximum number of missed cleavages were among the criteria used in the database search [ 14 ]. One or more peptides with an individual MASCOT score corresponding to p<0.05 were used to identify proteins, which were then annotated by UniProtKB/Swiss-Prot entries ( http://www.uniprot.org/ ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MASCOT software, version 2.2 (Matrix Science, London, UK), was used to search the peptide sequences against the NCBI mammal database for protein identification. Taxonomy (mammals), enzyme (trypsin), variable modifications (oxidation of methionine residues), mass values (monoisotopic), protein mass (unrestricted), peptide mass tolerance (1.2 Da), fragment mass tolerance (±0.6 Da), peptide charge state (1+, 2+ and 3+) and maximum number of missed cleavages were among the criteria used in the database search [ 14 ]. One or more peptides with an individual MASCOT score corresponding to p<0.05 were used to identify proteins, which were then annotated by UniProtKB/Swiss-Prot entries ( http://www.uniprot.org/ ).…”
Section: Methodsmentioning
confidence: 99%
“…ECL western blotting detection reagents (GE Healthcare) was utilized to visualized the target proteins. A ChemiDoc Touch Imaging System (Bio-Rad Laboratories) was used to image the chemiluminescent blots and Image Lab 6.0.1 software (Bio-Rad Laboratories) was used to analyse protein band intensities [ 14 ]. Total protein normalization was performed with the modification of Aldridge et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the use of salivary proteins as a potential diagnostic marker for oral cancer. The identification of proteins is either cleaved by gel electrophoresis or enzymatic digestion by the procedure to produce peptides (Hu et al, 2008;Ploypetch et al, 2020). Approximately, 3000 proteins have been identified in saliva by using various procedures (Hu et al, 2008;Jarai et al, 2012;Ploypetch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of proteins is either cleaved by gel electrophoresis or enzymatic digestion by the procedure to produce peptides (Hu et al, 2008;Ploypetch et al, 2020). Approximately, 3000 proteins have been identified in saliva by using various procedures (Hu et al, 2008;Jarai et al, 2012;Ploypetch et al, 2020). Similarly, various potential biomarkers identified from the saliva of OSCC such as cytokeratin 19 fragment (Cyfra21-1) (Rathore et al, 2020), albumin (Nguyen et al, 2020), telomerase (Sannam et al, 2016), transferrin (Nguyen et al, 2020), glutathione (Singh et al, 2020) were identified.…”
Section: Introductionmentioning
confidence: 99%